Changes in muscle-tendon length during the take-off of a running long jump - Hay, J. G.; Thorson, E. M.; Kippenhan, B. Ch. (Journal of Sports Sciences, 1999)
he aims of this study were to determine: (1) the modes of action of selected muscles of the supporting leg during the take-off of a running long jump; (2) whether the instant at which maximum knee flexion is recorded is a valid indicator of the instant these muscles change their modes of action; and (3) the relationships between the actions of these muscles and the change in the vertical velocity of the centre of mass during the take-off. Eleven elite, female long jumpers performed six jumps from a full-length approach. A model of selected muscles of the jumping leg was developed to estimate muscle-tendon lengths from segment positions obtained using cinematography. Only half of the muscles exhibited a lengthening-shortening sequence of activity. The instant at which maximum knee flexion was recorded was a poor indicator of when the muscles changed from eccentric to concentric activity. The more the vasti muscles were stretched, the larger the gain in vertical velocity; the longer the triceps surae muscles at touchdown, the more they were stretched, and the faster they were stretched, the larger the gain in vertical velocity. Enhancement through use of the stretch-shortening cycle did not make a significant contribution to vertical velocity via the actions of the vasti and triceps surae muscles.